Answer:
[tex]\huge\boxed{\sf f^{-1}(x)=36x^2+2}[/tex]
Step-by-step explanation:
Given function:
[tex]\displaystyle f(x)=\frac{\sqrt{x-2} }{6}[/tex]
Put f(x) = y.
[tex]\displaystyle y=\frac{\sqrt{x-2} }{6}[/tex]
Exchange x and y.
[tex]\displaystyle x=\frac{\sqrt{y-2} }{6}[/tex]
Solve for y.
[tex]\displaystyle x=\frac{\sqrt{y-2} }{6}[/tex]
Multiply both sides by 6.
[tex]\displaystyle x \times 6 = \sqrt{y-2} \\\\6x = \sqrt{y-2}[/tex]
Take square root on both sides.
[tex](6x)^2=(\sqrt{y-2} )^2\\\\36x^2 = y - 2[/tex]
Add 2 to both sides
[tex]36x^2+2 = y[/tex]
Put y = f⁻¹(x)
[tex]36x^2+2=f^{-1}(x)[/tex]
OR
[tex]f^{-1}(x)=36x^2+2\\\\\rule[225]{225}{2}[/tex]